Modified attapulgite and polypropylene flame-retardant composite material and preparation method thereof

By modifying the concave and concave rock stone, a modified concave and concave rock stone with excellent flame retardant properties is formed and added to the polypropylene matrix, which solves the problems of flammable and toxic fumes in traditional polypropylene flame retardant materials, and achieves efficient and environmentally friendly flame retardant effects and cost reduction.

CN119613815APending Publication Date: 2025-03-14天津大学浙江研究院 +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411802065.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional polypropylene flame retardant materials have problems with flammable properties and toxic fumes, and high content of halogen-free flame retardant increases material costs.

Method used

By using modified concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and

Benefits of technology

It realizes excellent flame retardancy, thermal stability and mechanical properties of polypropylene materials, reduces material costs, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The attapulgite (HNTs) is modified by using the diethyl aluminum hypophosphite (ADP), so that the flame retardant property of the HNTs and the compatibility of the HNTs and a polypropylene matrix can be remarkably improved. Through thermal modification, the treated surfaces of the HNTs can effectively adsorb phosphorus elements, and ADP can form phosphate groups on the surfaces of the HNTs to enhance the flame inhibition effect of the HNTs. Due to the adsorption effect, the modified HNTs can form a carbonized layer more quickly at high temperature, flame spreading is prevented, and the flammability of the material in a fire disaster is reduced. The dispersity and compatibility of the modified HNTs in a polypropylene matrix are remarkably improved, the mechanical property and thermal stability of the composite material are enhanced, and the modification cost is effectively reduced by optimizing the modification method. Compared with a traditional high-content inorganic flame retardant, the ADP modified HNTs has the advantages that the flame retardant property is improved, and meanwhile, the requirement for using other expensive flame retardants is reduced, so that the cost of the composite material is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer flame retardant materials, and particularly relates to a modified attapulgite and polypropylene flame retardant composite material and a preparation method thereof. Background Art

[0002] Flame-retardant polypropylene (PP) materials are widely used in industrial and consumer applications. Polypropylene is widely used in various products due to its chemical resistance, excellent electrical insulation, simple processing and moderate price. However, the flammable nature of polypropylene has, to a certain extent, limited its use in fields with high flame retardancy requirements, such as electronic appliances, automotive interiors, and building materials. In order to meet this demand, flame retardant modification of polypropylene has become one of the important research directions.

[0003] The application of traditional halogen-containing flame retardant systems in polypropylene has a long history. Although these flame retardants can effectively inhibit the spread of flames, they will produce toxic and corrosive smoke when burning, which poses a hidden danger to health and the environment. Due to increasingly stringent environmental regulations, halogen-containing flame retardants are gradually being replaced by halogen-free flame retardant technology. Halogen-free flame retardants include phosphorus-based, nitrogen-based and various flame retardant ingredients. They are currently considered to be an important research direction for flame retardant modification of polypropylene, but high content of halogen-free flame retardants will increase the cost of composite materials.

[0004] Attapulgite (HNTs) is a natural hydrous magnesium aluminum silicate mineral, a unique type of clay mineral. It has excellent physical and chemical properties due to its fibrous or needle-like crystal structure. The mineral is mainly distributed in China, the United States and other places. It has abundant reserves and low prices. It is an environmentally friendly, low-cost industrial material.

[0005] The unique pore structure and high specific surface area of ​​HNTs give them excellent adsorption, catalytic activity and rheological properties, and they are widely used in many fields, such as adsorbents, catalyst carriers, rheological modifiers, etc. In addition, HNTs also show potential in the field of flame retardant materials. Studies have shown that HNTs lose structural water at high temperatures, produce water vapor, and form an oxide isolation layer mainly composed of MgO and Al2O3, which blocks oxygen and thus plays a flame retardant role. The application of HNTs to polypropylene composites can appropriately reduce costs, but HNTs are prone to poor dispersion when added to polypropylene materials, which not only fails to effectively exert the flame retardant effect, but also reduces the performance of polypropylene materials.

[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0007] The purpose of the present invention is to provide a modified attapulgite and polypropylene flame retardant composite material and a preparation method thereof. After the modified attapulgite is added to the polypropylene matrix, the polypropylene can have excellent flame retardancy, thermal stability and mechanical properties, and has the advantages of low cost, environmental protection and good flame retardancy, and is suitable for fields requiring high flame retardancy such as electronics, automobiles and construction.

[0008] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:

[0009] A modified attapulgite, wherein the modified attapulgite is obtained by at least soaking and thermally modifying the attapulgite using a diethylphosphinate aluminum solution as a raw material;

[0010] During immersion, the mass ratio of aluminum diethylphosphinate to attapulgite is (0.5-1.5):10;

[0011] The thermal modification includes at least calcination.

[0012] In one or more embodiments of the present invention, the specific surface area of ​​the modified attapulgite is 150 to 200 m 2 / g.

[0013] In one or more embodiments of the present invention, the particle size of the modified attapulgite is 200-800 meshes.

[0014] In one or more embodiments of the present invention, the thermal modification further includes drying before calcination, and the drying temperature is 80-100° C. and the time is 4-12 hours.

[0015] In one or more embodiments of the present invention, the thermal modification further comprises a heat treatment after drying and before calcination, the heat treatment temperature is 120-180° C., and the time is 30-60 min.

[0016] In one or more embodiments of the present invention, the calcination temperature is 200-300° C. and the calcination time is 2-4 hours.

[0017] Another specific embodiment of the present invention provides a technical solution as follows:

[0018] A method for preparing modified attapulgite comprises the following steps:

[0019] Dissolving aluminum diethylphosphinate in a solvent to prepare an aluminum diethylphosphinate solution;

[0020] According to the mass ratio of aluminum diethylphosphinate to attapulgite being (0.5-1.5):10, attapulgite is added to the aluminum diethylphosphinate solution, stirred, filtered, and a primary product is obtained;

[0021] The primary product is thermally modified to obtain modified attapulgite.

[0022] In one or more embodiments of the present invention, the attapulgite is pretreated: the attapulgite is washed with deionized water and then dried at 80-100° C. for 4-12 hours.

[0023] Another specific embodiment of the present invention provides a technical solution as follows:

[0024] A polypropylene flame-retardant composite material, comprising the following components in weight percentage: 55-70% polypropylene, 10-15% modified attapulgite, 5-10% flame retardant, 10-20% elastomer, 2-5% compatibilizer, 0.5-2% antioxidant, 0.5-2% anti-dripping agent, and 0.2-1.5% release agent;

[0025] The modified attapulgite is the modified attapulgite mentioned above or the modified attapulgite prepared by the preparation method of the modified attapulgite mentioned above.

[0026] Another specific embodiment of the present invention provides a technical solution as follows:

[0027] A method for preparing a polypropylene flame retardant composite material comprises the following steps:

[0028] Mix polypropylene, elastomer and compatibilizer at 500-800 rpm for 4-5 minutes;

[0029] Then, adding modified attapulgite, flame retardant, antioxidant, anti-dripping agent and release agent, mixing at a speed of 600 to 1000 rpm for 5 to 10 minutes to obtain a mixture;

[0030] The mixed materials are melt-blended and extruded at 180-230° C. to obtain a polypropylene flame-retardant composite material.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) Excellent flame retardant properties: The surface modification of HNTs by aluminum diethylphosphinate (ADP) enhances its compatibility with the polypropylene matrix, and the introduction of phosphate groups improves the flame retardant effect of the composite material, which can significantly delay the spread of flames and achieve a higher flame retardant grade (such as V-0 or V-1), effectively improving the flame retardant properties of polypropylene composites;

[0033] (2) Enhanced thermal stability and mechanical properties: Modified attapulgite not only improves the thermal stability of the composite material, but also improves the mechanical properties of the composite material through optimized formulation and processing technology. In particular, during the twin-screw extrusion process, the optimized temperature zone setting ensures the uniform distribution of the filler, effectively avoids the problem of increased brittleness, and improves the toughness and durability of the material.

[0034] (3) Good processing performance and fluidity: The modified attapulgite is evenly dispersed in polypropylene by adopting a specific pretreatment and step-by-step mixing method, which significantly improves the processing performance and fluidity of the composite material, avoids blockage or uneven dispersion during the extrusion process, and ensures the feasibility and efficiency of large-scale production;

[0035] (4) Cost-effectiveness and environmental advantages: The present invention reduces material costs while ensuring high flame retardant properties through reasonable formula ratios and effective process optimization. It uses natural mineral HNTs as fillers and has good environmental performance, which meets the needs of the modern plastics industry for green and environmentally friendly materials. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0037] Aluminum diethylphosphinate (ADP) is a solid organic phosphorus flame retardant with high temperature resistance (above 400°C), hydrophobicity and strong migration resistance. Due to its high thermal stability, chemical stability and environmental friendliness, ADP can be used as a flame retardant for polymer materials to replace halogen flame retardants that are harmful to the environment. At the same time, the flame retardant process of ADP is relatively complicated. The main chemical bonds in its structure are PC, P=O, and PO. It has the basic flame retardant characteristics of phosphorus flame retardants and has both gas phase flame retardancy and condensed phase flame retardancy. ADP is thermally decomposed at high temperatures. The (PO*) free radicals formed by PO can capture the more active O and OH free radicals in the air, which can reduce the oxygen content in the confined space to a certain extent and terminate the chain reaction of combustion. At the same time, during the reaction of ADP with high temperature and oxygen, a condensed phase non-flammable liquid membrane is formed, which is coated on the surface of the burning object to isolate the air and achieve a flame retardant effect. ADP is an excellent substitute for halogen flame retardants due to its excellent properties such as high heat resistance, good dispersibility, high efficiency flame retardancy, non-toxicity, low smoke, and good compatibility.

[0038] As a phosphorus-based environmentally friendly halogen-free flame retardant, ADP shows significant advantages among halogen-free flame retardants. ADP is not only environmentally friendly and halogen-free, meeting the current demand for environmentally friendly flame retardants, but also has high heat resistance and dispersibility, can remain stable at high temperatures, and is evenly distributed in a variety of plastics and resins to improve flame retardant efficiency. Its efficient flame retardant performance allows good flame retardant effects to be achieved at lower addition amounts, reducing the burning rate and flame propagation of materials. At the same time, ADP produces less toxic gases and smoke during the combustion process, which improves the safety of the material and reduces secondary damage during fire. In addition, ADP has good compatibility with a variety of matrix resins, does not affect the mechanical properties of the material, and maintains the strength and toughness of the matrix material. The high phosphorus content of ADP makes it flame retardant in both the gas phase and the condensed phase, and achieves flame retardancy by forming a carbon layer and capturing free radicals. ADP has high thermal stability and hydrolysis resistance, which enables it to be used efficiently in occasions with high processing temperatures.

[0039] The present invention uses ADP to modify HNTs and then applies them to polypropylene composite materials to show significant advantages.

[0040] First, the combination of ADP and HNTs can produce a synergistic flame retardant effect, which can significantly improve the UL94 flame retardant rating of the composite material to V-0, and greatly improve the limiting oxygen index (LOI), showing excellent flame retardant properties. In addition, the addition of ADP-modified HNTs not only enhances the mechanical properties of polypropylene composites, such as tensile strength and elongation at break, but also helps the material maintain stability and durability during use.

[0041] In terms of thermal stability, the addition of HNTs promotes the carbonization process and slows down the thermal degradation of polypropylene composites, thereby improving the thermal stability of the material. The ADP-HNTs flame retardant system can also form a continuous and dense carbon layer, which acts as a heat and oxygen barrier during the combustion process, effectively preventing the spread of flames. HNTs can interact with ADP in the condensed phase, promote cross-linking carbonization, and further enhance the flame retardant effect.

[0042] The modification of HNTs by ADP can significantly improve its compatibility and dispersibility in the polypropylene system. Due to the introduction of alkyl groups into the molecular structure of ADP, its hydrophobicity and thermal decomposition temperature are greatly improved, so that it will not migrate and absorb moisture when used in polymer materials, and is particularly suitable for environments with high processing temperatures. At the same time, ADP will not affect the insulation properties of polypropylene composites, which is crucial for applications in electronic and electrical fields. Finally, ADP has good compatibility with polypropylene matrix resins, can maintain the mechanical properties of the matrix material, and avoid the degradation of material performance caused by the addition of flame retardants.

[0043] In general, ADP-modified HNTs as flame-retardant components in the preparation of polypropylene composite materials not only provide efficient flame retardant properties, but also enhance the mechanical properties and thermal stability of the material, while maintaining environmental friendliness and the insulation properties of the material, showing a wide range of application prospects. The introduction of modified attapulgite into polypropylene can achieve excellent flame retardant and thermal stability effects while maintaining the mechanical properties of the material. This inorganic mineral-based flame retardant modification route meets green environmental protection requirements and gives polypropylene materials greater application potential in the fields of electronics, automobiles, and construction.

[0044] A specific embodiment of the present invention provides a modified attapulgite, which is obtained by taking a diethyl phosphinate aluminum solution as a raw material, at least soaking the attapulgite and thermally modifying it; during the soaking, the mass ratio of the diethyl phosphinate aluminum to the attapulgite is (0.5-1.5):10; and the thermal modification at least includes calcination.

[0045] Furthermore, the thermal modification also includes drying before calcination, the drying temperature is 80-100°C, and the time is 4-12 hours; the thermal modification also includes heat treatment after drying and before calcination, the heat treatment temperature is 120-180°C, and the time is 30-60 minutes; the calcination temperature is 200-300°C, and the time is 2-4 hours.

[0046] Specifically, the specific surface area of ​​the modified attapulgite is 150 to 200 m 2 / g, with a particle size of 200-800 mesh. ADP, as a phosphorus-containing organic compound, can react with the functional groups on the surface of HNTs at high temperatures to form a surface chemical structure with phosphate groups, which not only effectively improves the surface hydrophilicity and dispersibility of HNTs, but also enhances its compatibility with the polypropylene matrix. In addition, the introduction of phosphate groups can improve the flame retardancy of attapulgite. When applied to polypropylene materials, it can effectively improve the flame retardancy of polypropylene materials, promote the formation of a protective carbonized layer of polypropylene materials under high temperature environments, and reduce gas release during thermal decomposition.

[0047] With respect to the mass ratio of ADP to attapulgite, in terms of adsorption performance, a lower amount of ADP may be suitable for applications that require lower costs and have basic flame retardant properties. In this case, a reduced amount of ADP may reduce the adsorption performance of attapulgite because fewer phosphorus-containing groups are generated by the reaction of ADP with the surface of attapulgite, which help form an insulating layer during combustion and inhibit the combustion reaction. A higher amount of ADP can be used for materials that require higher flame retardant properties, which can significantly improve the flame retardant effect and the thermal stability of the material. Increasing the amount of ADP can increase the phosphorus-containing groups on the surface of attapulgite, which can more effectively generate insulating layers such as phosphoric acid during combustion, thereby improving flame retardant properties.

[0048] In terms of thermal stability, low ADP dosage may mean lower thermal stability improvement, because less ADP means less phosphorus is introduced into the attapulgite, which helps to form a stable phosphate layer at high temperature and improve the thermal stability of the material. High ADP dosage can significantly improve the thermal stability of the material, because more phosphorus is introduced, which helps to form a more stable phosphate layer at high temperature, thereby improving the thermal stability of the material.

[0049] In terms of surface reactivity, low ADP dosage may mean lower surface reactivity because less ADP reacts with the attapulgite surface, resulting in fewer surface active sites. High ADP dosage can increase the surface reactivity of attapulgite because more ADP reacts with the attapulgite surface, increasing the surface active sites and helping to improve the flame retardant properties of the material.

[0050] In terms of economics and environmental protection, low ADP dosage may be more economical because the amount of ADP used is reduced, and may have less impact on the environment because less chemicals are used. High ADP dosage may be more expensive, but can provide better performance, especially in applications requiring high flame retardancy.

[0051] In summary, different ADP contents will affect the adsorption performance, thermal stability and surface reactivity of modified attapulgite, and thus affect its application effect in flame retardant materials and other fields. Low ADP content may be more economical and suitable for applications with basic flame retardant performance requirements, while high ADP content is suitable for applications with higher flame retardant performance requirements, which can be adjusted within the above range according to actual needs.

[0052] Another specific embodiment of the present invention provides a method for preparing modified attapulgite, comprising steps 1-4.

[0053] Step 1, pretreatment of HNTs: the attapulgite is washed with deionized water, then dried at 80-100° C. for 4-12 hours, and then the dried attapulgite is crushed to a size of more than 200 meshes.

[0054] Specifically, attapulgite with a particle size of 1 to 10 μm is selected, and impurities on the surface of HNTs and soluble impurities can be removed by repeated washing with deionized water; the moisture content is controlled below 5% by drying to prevent excessive moisture from affecting the modification effect; the HNTs are crushed to ensure uniform particle size and increase specific surface area, thereby enhancing the adsorption and surface reactivity of HNTs to ADP.

[0055] Step 2, preparation of ADP solution: according to the mass ratio of ADP to attapulgite of (0.5-1.5):10, weigh ADP, dissolve ADP in an organic solvent, and prepare an ADP solution with a concentration of 5-10%.

[0056] Specifically, ADP is dissolved in an organic solvent to facilitate the reaction with HNTs. The organic solvent is selected from anhydrous ethanol or acetone, and a magnetic stirring device is used to evenly disperse ADP in the organic solvent to avoid excessive local concentration and ensure uniformity and stability of the modification process.

[0057] Step 3, modification of HNTs: add HNTs to the ADP solution, continue stirring for 2 to 4 hours, filter, and obtain a primary product.

[0058] Specifically, a magnetic stirring device is used to continuously stir at room temperature to ensure that ADP fully reacts with the surface of HNTs. During this process, ADP reacts with HNTs to modify their surface. The introduced phosphorus element can effectively generate thermal insulation layers such as phosphoric acid during combustion, helping to inhibit the combustion reaction. In addition, ADP will form complexes or precipitates with metal ions on the surface of attapulgite, enhancing the adsorption performance of attapulgite, and further adsorbing more phosphorus-containing groups, further improving flame retardant properties. Finally, the reaction mixture is filtered in a vacuum filtration device to remove excess solvent.

[0059] Step 4, drying and calcination treatment: add the primary product to the ADP solution, dry it at 80-100°C for 4-12h, then heat treat it at 120-180°C for 10-50min, and then calcine it at 200-300°C for 2-4h. After calcination, take out the sample and cool it naturally at room temperature to obtain modified attapulgite.

[0060] Specifically, treatment at different temperatures can selectively remove different types of moisture in the tunnels within the crystals, thereby changing the pore structure and surface properties, increasing the specific surface area of ​​HNTs, improving the pore structure and surface properties, and increasing active centers and adsorption sites. Among them, the drying process can remove residual solvents and control the moisture content, the heat treatment process can promote the chemical reaction, and the calcination process helps to promote the formation of phosphate groups and bind to the surface of HNTs, which helps to form a stable surface attachment layer. The modified attapulgite obtained after treatment in step 4 can show good dispersibility in polypropylene, and release phosphorus-containing substances during combustion, effectively enhancing flame retardant properties. By controlling the calcination temperature, the decomposition of ADP can be reduced, ensuring the modification effect.

[0061] Furthermore, in step 3, during the process of soaking HNTs in ADP solution, the phosphate groups in ADP interact with functional groups such as hydroxyl groups on the surface of HNTs to form a relatively loose bond. After the treatment in step 4, the moisture adsorbed on the surface of attapulgite is removed by drying, so that the bond between ADP and the surface of attapulgite becomes tighter. After heat treatment and calcination, attapulgite loses adsorbed water, zeolite water and crystallization water in its structure, so that ADP penetrates deeper into the pores of attapulgite, and the interaction between ADP and attapulgite is further enhanced, and finally a stable surface adhesion layer is formed.

[0062] In addition, in step 3, ADP can also enhance the adsorption performance of attapulgite by forming complexes or precipitates with metal ions on the surface of HNTs, thereby allowing attapulgite to further adsorb more phosphorus-containing groups. During calcination in step 4, it helps to form a surface adhesion layer rich in phosphate groups, further improving flame retardancy and compatibility.

[0063] Another specific embodiment of the present invention provides a polypropylene flame retardant composite material, comprising the following components in weight percentage: 55-70% polypropylene, 10-15% modified attapulgite, 5-10% flame retardant, 10-20% elastomer, 2-5% compatibilizer, 0.5-2% antioxidant, 0.5-2% anti-dripping agent, and 0.2-1.5% release agent.

[0064] Specifically, adding modified attapulgite to polypropylene can achieve a balance between the material's efficient flame retardant properties and lower production costs; the elastomer can improve the material's toughness and impact resistance, avoiding brittle cracking of the material in high-strength applications; the compatibilizer can improve the compatibility between the components, making the material more uniform in microstructure, thereby achieving good flame retardant properties and mechanical properties; the flame retardant can produce a synergistic effect with the modified attapulgite, so that the flame retardant properties of the composite material reach higher standards; adding an appropriate amount of antioxidant and anti-drip agent can improve the antioxidant performance and anti-drip effect of the composite material; adding a release agent can improve the processing performance of the composite material, avoid adhesion in the mold, and improve production efficiency.

[0065] Furthermore, the elastomer is one or a combination of EPDM (ethylene propylene rubber), SBS (styrene-butadiene-styrene block copolymer), TPE (thermoplastic elastomer), preferably EPDM, which has good low-temperature flexibility, weather resistance and good compatibility with polypropylene.

[0066] Further, the compatibilizer is one or a combination of maleic anhydride grafted polyethylene (PE-g-MAH), maleic anhydride grafted polypropylene (PP-g-MAH), and ethylene / vinyl acetate copolymer (EVA). PE-g-MAH is preferably used, which can effectively improve the compatibility of modified attapulgite and polypropylene and enhance the dispersibility of the material.

[0067] Furthermore, the flame retardant is one or a combination of phosphorus flame retardants, nitrogen flame retardants, and chlorinated paraffin. Preferably, phosphorus flame retardants such as melamine phosphate are used, which have good flame retardant effects and can effectively inhibit the spread of flames by forming a carbonized layer.

[0068] Furthermore, the antioxidant is one or a combination of BHT (tert-butyl hydroquinone), Irganox 1010, THIOPA (thioalcohol), etc. Preferably, Irganox 1010 is used, which has excellent antioxidant properties and can effectively extend the service life of polypropylene in a high temperature environment.

[0069] Further, the anti-dripping agent is one or a combination of expanded graphite, melamine phosphate, and silicate. Expanded graphite is preferably used, which can expand and form a solid carbonized layer when a fire occurs to prevent the spread and dripping of flames.

[0070] Furthermore, the demoulding agent is one or a combination of zinc stearate, polyethylene wax, and silicone oil. Preferably, the combination of zinc stearate and polyethylene wax can effectively improve the fluidity of the polypropylene composite material, avoid die blockage during extrusion, and have a good demoulding effect.

[0071] Another specific embodiment of the present invention provides a method for preparing a polypropylene flame retardant composite material, comprising the following steps:

[0072] Mix polypropylene, elastomer and compatibilizer at a speed of 500-800 rpm for 4-5 minutes to make the raw materials preliminarily mixed;

[0073] Then, adding modified attapulgite, flame retardant, antioxidant, anti-dripping agent and release agent, mixing at a speed of 600 to 1000 rpm for 5 to 10 minutes to make all the raw materials evenly distributed, to obtain a mixture;

[0074] The mixed material is put into a twin-screw extruder and melted at 180-230°C to ensure that the material is evenly dispersed in the screw to avoid blockage of the die or poor dispersion caused by local uneven distribution. Finally, the polypropylene flame-retardant composite material is prepared through an extrusion molding process.

[0075] Specifically, the present invention realizes the uniform dispersion of modified attapulgite in a polypropylene (PP) matrix through a specific pretreatment and step-by-step mixing method, optimizes the distribution of polypropylene, elastomer and compatibilizer, and significantly improves the processing performance and fluidity of the material. During the twin-screw extrusion process, the optimized temperature zone setting ensures the full plasticization and uniform dispersion of the components, effectively improves the thermal conductivity, flame retardancy and toughness of the composite material, solves the problem of increased brittleness of the material after the addition of fillers in the traditional method, and provides an innovative preparation scheme for thermally conductive flame-retardant polypropylene composite materials, which have both excellent flame retardancy and good mechanical properties.

[0076] The present invention is further described in detail below in conjunction with specific embodiments.

[0077] In the embodiments and comparative examples, the polypropylene used is SP179, the flame retardant is FR-1420, the elastomer is EDPM 3430, the compatibilizer is maleic anhydride grafted polyethylene, the brand is CMG5904, the antioxidant is Irganox 1010, the anti-dripping agent is 150 mesh expanded graphite, and the release agent is a mixture of zinc stearate and polyethylene wax in a mass ratio of 20:8, and the polyethylene wax brand is PE-36A.

[0078] Preparation example of modified attapulgite

[0079] Preparation Example 1

[0080] The HNTs were washed with deionized water and then dried at 90° C. for 6 h to reduce the moisture content to less than 5%. After drying, the HNTs were crushed to 300 mesh.

[0081] According to the mass ratio of ADP to HNTs of 10:90, ADP was dissolved in anhydrous ethanol to prepare an ADP solution with a mass concentration of 10%. HNTs were added to the ADP solution, and stirred at 500 rpm for 3 hours using magnetic stirring and ultrasonic assistance to fully react. Then vacuum filtration was performed to remove the solvent to obtain the primary product.

[0082] The primary product was dried at 90°C for 4 hours, heat treated at 160°C for 30 minutes, and finally calcined at 250°C under nitrogen protection for 3 hours to obtain modified attapulgite.

[0083] Preparation Example 2

[0084] The HNTs were washed with deionized water and then dried at 90° C. for 8 h to reduce the moisture content to less than 5%. After drying, the HNTs were crushed to 300 mesh.

[0085] According to the mass ratio of ADP to HNTs of 0.5:10, ADP was dissolved in anhydrous ethanol to prepare an ADP solution with a mass concentration of 5%. HNTs were added to the ADP solution, and stirred at 500 rpm for 3 hours using magnetic stirring and ultrasonic assistance to fully react. Then vacuum filtration was performed to remove the solvent to obtain a primary product.

[0086] The primary product was dried at 90°C for 8 hours, heat treated at 150°C for 30 minutes, and finally calcined at 250°C under nitrogen protection for 3 hours to obtain modified attapulgite.

[0087] Preparation Example 3

[0088] The HNTs were washed with deionized water and then dried at 95° C. for 10 h to reduce the moisture content to less than 5%. After drying, the HNTs were crushed to 300 mesh.

[0089] According to the mass ratio of ADP to HNTs of 1.5:10, ADP was dissolved in anhydrous ethanol to prepare an ADP solution with a mass concentration of 10%. HNTs were added to the ADP solution, and stirred at 500 rpm for 4 hours using magnetic stirring and ultrasonic assistance to fully react. Then vacuum filtration was performed to remove the solvent to obtain the primary product.

[0090] The primary product was dried at 95°C for 10 hours, then heat treated at 170°C for 40 minutes, and finally calcined at 300°C under nitrogen protection for 4 hours to obtain modified attapulgite.

[0091] Polypropylene flame retardant composite material embodiment

[0092] Example 1

[0093] The polypropylene flame retardant composite material comprises the following components in weight percentage: 60% polypropylene, 12% modified attapulgite in Preparation Example 1, 8.5% flame retardant, 15% elastomer EDPM, 2% compatibilizer, 1% antioxidant, 1% anti-dripping agent, and 0.5% release agent.

[0094] Add polypropylene, elastomer EDPM and compatibilizer into a high-speed mixer and mix at 600 rpm for 5 minutes for preliminary mixing. Then add modified attapulgite, flame retardant, antioxidant, anti-drip agent and release agent and mix at 800 rpm for 7 minutes to evenly distribute all components to obtain a mixture.

[0095] The mixed materials were put into a twin-screw extruder, melt-blended at 200° C., and a polypropylene flame-retardant composite material was prepared through an extrusion molding process.

[0096] Examples 2-8, Comparative Examples 1-3

[0097] The operations for preparing the polypropylene flame retardant composite materials in Examples 2-8 and Comparative Examples 1-3 are the same as those in Example 1, except that the selection of the modified attapulgite and the weight percentages of the raw material components are different, as shown in Table 1.

[0098] Table 1 Raw materials weight percentage of Examples 1-8 and Comparative Examples 1-3

[0099]

[0100]

[0101] The performance tests were carried out on the polypropylene flame retardant composite materials obtained in each embodiment and each comparative example:

[0102] Density: Tested in accordance with GB / T 1033.1-2008 standard;

[0103] Melting point: tested according to GB / T 19466.3-2004 standard;

[0104] Yield strength, tensile modulus, elongation at break: tested in accordance with the provisions of GB / T1040.2-2006, with a test speed of 50 mm / min;

[0105] Bending strength and bending modulus test: Tested according to GB / T 9341 three-point bending, with a test speed of 2mm / min and a span of 64mm;

[0106] Notched impact strength: Tested according to the provisions of GB / T1843-2006, the test temperature is 23°C;

[0107] Limiting Oxygen Index (LOI): Tested based on the internationally accepted test standards ISO 4589-2 and ASTM D2863;

[0108] Flame retardant performance test: According to GB / T2408-2008 standard, the sample size is 125*13*1.6mm.

[0109] Table 2 Performance test results of polypropylene flame retardant composite materials

[0110]

[0111]

[0112] Compared with Example 1, the proportion of polypropylene in Comparative Example 1 is the highest, reaching 72%, which provides good processing fluidity and cost-effectiveness for the material. No modified HNTs are added, highlighting the high proportion of polypropylene to provide excellent fluidity and cost-effectiveness, but the lack of modified HNTs limits its flame retardant properties. The flame retardant FR-1420 is used as the main flame retardant. Although the flame retardant properties are close, the amount of flame retardant is small, so the flame retardancy is not as good as that of Example 1 with HNTs added, and the lack of synergy with the flame retardant causes the flame retardancy to only reach V-1. Although modified HNTs are introduced in Comparative Example 2, there is a lack of flame retardants. HNTs are directly mixed in the formula, and the flame retardant performance is weak, and the mechanical properties are relatively balanced. The composite material in Comparative Example 3 performs best in flame retardant properties because it contains both modified HNTs and flame retardant FR-1420. However, due to the lack of compatibilizers, the compatibility and dispersibility of the material are affected, thereby affecting the mechanical properties and processing properties.

[0113] The flame-retardant polypropylene composite materials prepared in Examples 1-3 and 7-8 all have excellent comprehensive properties. ADP is used to modify attapulgite, phosphate compounds are formed on the surface of attapulgite, and phosphoric acid groups are introduced. When the material burns, the phosphorus content can be released and a heat-insulating layer can be formed, which can effectively inhibit the spread of flames and reach the UL-94V-0 or V-1 flame-retardant standard. At the same time, the modified attapulgite improves the thermal stability of the composite material, reduces thermal degradation, and can adapt to higher temperatures. The addition of modified attapulgite also significantly improves the mechanical properties of polypropylene, including impact toughness, tensile strength and flexural strength, so that the material has good mechanical properties while maintaining flame retardant properties. In addition, combined with the pretreatment and mixing process, the modified attapulgite can be evenly dispersed in polypropylene, improving the fluidity and processing performance of the material.

[0114] Further analysis shows that modified attapulgite improves the flame retardant properties of polypropylene through multiple mechanisms. First, modified attapulgite enhances the thermal stability of the material and delays the thermal decomposition process; second, modified attapulgite combines with polypropylene chains at high temperatures to form a dense carbon layer, which effectively isolates heat and oxygen and prevents the spread of flames; in addition, modified attapulgite can produce a synergistic effect with other flame retardants such as intumescent flame retardant (FR-1420), further improving the flame retardant properties of the material, especially in reducing the peak heat release rate and smoke release rate; during the combustion process, modified attapulgite may also react chemically with the flame retardant FR-1420. The modified attapulgite interacts with each other to generate new chemical substances, which enhances the thermal stability and mechanical strength of the carbon layer; at the same time, the modified attapulgite can also improve the limiting oxygen index (LOI) of polypropylene, which is an important indicator for measuring the flame retardant properties of materials; the modified attapulgite can be evenly dispersed in the polypropylene matrix, improving the compatibility of the material. Compared with the direct addition of unmodified attapulgite and ADP, it can take into account both dispersibility and flame retardancy and reduce the occurrence of attapulgite agglomeration; in addition, HNTs as a carrier can also control the release rate of flame retardant substances to achieve a multi-level flame retardant effect.

[0115] In addition, the addition of modified attapulgite and flame retardant FR-1420 improves the flame retardant properties of the material, while the addition of elastomer EPDM improves the toughness and impact resistance of the material and solves the brittleness problem. The addition of compatibilizer PE-g-MAH improves the compatibility between polymer and filler, antioxidant Irganox 1010 improves the thermal stability of the material, anti-dripping agent expanded graphite enhances the flame retardancy of the material, and release agent improves the processing performance of the composite material.

[0116] The raw material composition of the polypropylene flame retardant composite material in Examples 4-6 is similar to that in Examples 1-3, but the specific proportions are adjusted to optimize the comprehensive properties of the material, including mechanical properties, thermal properties and flame retardant properties.

[0117] In summary, the change in formula mainly affects the flame retardancy, mechanical properties and processing fluidity of the material. HNTs have poor compatibility with polypropylene, poor processing fluidity, and will clog the equipment. Therefore, the present invention uses ADP to modify HNTs, increase its flame retardancy and compatibility with other components, and improve the compatibility and dispersibility between components by adding a certain amount of compatibilizer, thereby improving the mechanical properties of the material. At the same time, the modified attapulgite synergistic flame retardant can improve the flame retardancy of the material, play a role in reducing costs, and finally can prepare a polypropylene-based flame retardant composite material with excellent comprehensive performance to meet the needs of different application fields.

[0118] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0119] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A modified attapulgite, characterized in that: The modified attapulgite is obtained by at least soaking and thermally modifying the attapulgite using aluminum diethylphosphinate solution as a raw material; During immersion, the mass ratio of aluminum diethylphosphinate to attapulgite is (0.5-1.5):10; The thermal modification includes at least calcination.

2. The modified attapulgite according to claim 1, characterized in that: The specific surface area of ​​the modified attapulgite is 150 to 200 m 2 / g.

3. The modified attapulgite according to claim 1, characterized in that: The particle size of the modified attapulgite is 200-800 meshes.

4. The method for preparing modified attapulgite according to claim 1, characterized in that: The thermal modification also includes drying before calcination, with the drying temperature being 80-100° C. and the drying time being 4-12 hours.

5. The method for preparing modified attapulgite according to claim 4, characterized in that: The thermal modification also includes heat treatment after drying and before calcination, with the heat treatment temperature being 120-180° C. and the time being 30-60 minutes.

6. The method for preparing modified attapulgite according to claim 1, characterized in that: The calcination temperature is 200-300°C and the time is 2-4 hours.

7. A method for preparing modified attapulgite, characterized in that: The steps include: Dissolving aluminum diethylphosphinate in a solvent to prepare an aluminum diethylphosphinate solution; According to the mass ratio of aluminum diethylphosphinate to attapulgite being (0.5-1.5):10, attapulgite is added to the aluminum diethylphosphinate solution, stirred, filtered, and a primary product is obtained; The primary product is thermally modified to obtain modified attapulgite.

8. The method for preparing modified attapulgite according to claim 7, characterized in that: The attapulgite is first pretreated: the attapulgite is washed with deionized water and then dried at 80-100° C. for 4-12 hours.

9. A polypropylene flame retardant composite material, characterized in that: The invention comprises the following components in weight percentage: 55-70% polypropylene, 10-15% modified attapulgite, 5-10% flame retardant, 10-20% elastomer, 2-5% compatibilizer, 0.5-2% antioxidant, 0.5-2% anti-dripping agent and 0.2-1.5% release agent; The modified attapulgite is the modified attapulgite described in any one of claims 1 to 6 or the modified attapulgite prepared by the preparation method of the modified attapulgite described in any one of claims 7 to 8.

10. A method for preparing the polypropylene flame retardant composite material according to claim 9, characterized in that: The steps include: Mix polypropylene, elastomer and compatibilizer at 500-800 rpm for 4-5 minutes; Then, adding modified attapulgite, flame retardant, antioxidant, anti-dripping agent and release agent, mixing at a speed of 600 to 1000 rpm for 5 to 10 minutes to obtain a mixture; The mixed materials are melt-blended and extruded at 180-230° C. to obtain a polypropylene flame-retardant composite material.

Citation Information

Cited By

  • Magnesium oxide heat-conducting insulating material as well as preparation method and application thereof

    CN120623651A

  • Magnesium oxide heat-conducting insulating material, preparation method and application thereof

    CN120623651B